A de novo mutation in PRICKLE1 associated with myoclonic epilepsy and autism spectrum disorder. (2nd October 2018) - Todd, Brittany P.; Bassuk, Alexander G.
Abstract: Homozygous recessive mutations in the PRICKLE1 gene were first described in three consanguineous families with myoclonic epilepsy. Subsequent studies have identified neurological abnormalities in humans and animal models with both heterozygous and homozygous mutations in PRICKLE1 orthologs. We describe a 7-year-old with a novel de novo missense mutation in PRICKLE1 associated with epilepsy, autism spectrum disorder and global developmental delay.